Is oral rehydration therapy associated with early childhood caries in children resident in Ile‐Ife, Osun State, Nigeria?. Issue 1 (6th July 2022) - Folayan, Morenike Oluwatoyin; Finlayson, Tracy; Oginni, Ayodeji Babatunde; Alade, Michael Abimbola; Adeniyi, Abiola Adetokunbo; El Tantawi, Maha
Abstract: Background: Oral rehydration therapy may increase the risk of early childhood caries (ECC) because of reduced pH in the oral environment. Aim: To investigate associations between the use of oral rehydration therapy and the prevalence and severity of ECC in children resident in the Ife Central Local Government Area of Osun State, Nigeria. Design: This observational study assessed the prevalence and severity of caries, using the International Caries Detection and Assessment System (ICDAS) II index. The outcome variables were the prevalence and severity of ECC. The explanatory variable was the use of oral rehydration solution for the management of diarrhea in the 12 months preceding the study. A multivariable logistic regression analysis was conducted to determine associations between the explanatory and outcome variables. Results: Only 217 (14%) of the 1564 children had used oral rehydration solution for the management of diarrhea. Seventy‐three (4.7%) children had ECC. The use of oral rehydration solution was not significantly associated with the prevalence and severity of ECC. Conclusion: The study findings suggest that the use of oral rehydration therapy in the management of diarrhea may not be a risk factor for ECC in communities with low prevalence and severity of ECC and high prevalence of gastroenteritis.